Simultaneous assessment of cardiac metabolism and perfusion using copolarized [1‐13C]pyruvate and 13C‐urea. Issue 1 (7th January 2016) - Lau, Angus Z.; Miller, Jack J.; Robson, Matthew D.; Tyler, Damian J.
Abstract : Purpose: To demonstrate the feasibility of imaging a bolus of co‐polarized [1‐ 13 C]pyruvate and 13 C‐urea to simultaneously assess both metabolism and perfusion in the rodent heart. Methods: Copolarized [1‐ 13 C]pyruvate and 13 C‐urea was imaged using a multi‐echo, flow‐sensitized spiral pulse sequence. Healthy rats were scanned in a two‐factor factorial design (n = 12 total; metabolism: overnight fasting versus fed with dichloroacetate injection; perfusion: rest versus adenosine stress‐induced hyperemia). Results: Alterations in metabolism were detected by changes in pyruvate metabolism into 13 C‐bicarbonate. Statistically independent alterations in perfusion were detected by changes in myocardial pyruvate and urea signals. Conclusion: The new pulse sequence was used to obtain maps of metabolism and perfusion in the rodent heart in a single acquisition. This hyperpolarized 13 C imaging test is expected to enable new studies in which the cardiac metabolism/perfusion mismatch can be studied in the acute environment. Magn Reson Med 77:151–158, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine